Problematika výroby nového popílkového pórobetonu - Bednárik, Vít (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Diplomová práce se zabývá možností laboratorního ověření vlivu charakteru vstupních surovin, zejména vápna a popílků, na kvalitu popílkového pórobetonu. Experimentální studie spočívá ve zhotovení série vzorků autoklávovaných a neautoklávovaných pórobetonů během dvou poloprovozních ověřování ve výrobním závodě, jejich zkoušením a porovnáním s výsledky neautoklávovaného pórobetonu vyrobeného laboratorně. Na základě dosažených poznatků byla vytvořena metodika komparace technologicky vyrobeného autoklávovaného pórobetonu a laboratorně zhotoveného neautoklávovaného pórobetonu.

The master´s thesis deals with the possibility of laboratory verification of the influence of feedstock character, especially lime and fly ash, on quality of fly ash aerated concrete. The experimental study involves taking a series of samples autoclaved and non-autoclaved aerated concrete during two pilot plant verification in the factory. After removal of autoclaved and non-autoclaved aerated concrete samples they were tested and compared with results of non-autoclaved aerated concrete produced in the laboratory. Methodology of comparison technologically-produced autoclaved aerated concrete and laboratory-produced non-autoclaved aerated concrete was designed based on achieved findings.
The issue of new fly ash aerated concrete production
Keywords: Autoklávovaný pórobeton; neautoklávovaný pórobeton; popílek; vápno; autoklávování; zrání hmoty; metodika; Autoclaved aerated concrete; non-autoclaved aerated concrete; fly ash; lime; autoclaving; maturation material; methodology